Living between Science and Belief - Sandra Troskie (Journal for the Study of Religion)
We live in an interregnum between the claims of science and those of faith. With this conviction, Charles Villa-Vicencio has commenced with a book, as John De Gruchy succinctly puts it in the Introduction, which was born out of the writer’s ‘long and often painful personal struggle...to relate religious faith to science’ (Villa-Vicencio 2021:ix). As such, Living between science and belief is therefore aimed at ‘believers trying to deal honestly with doubt’ (Villa-Vicencio 2021:ix).